2020
DOI: 10.1177/1474704919900633
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Mini-K-J and Its Utility for Measuring Fast Life History Traits in Japanese Undergraduate Students

Abstract: Life history theory is useful for taking an evolutionary approach to individual differences. An individual’s life history strategy (LHS), based on life history theory, can be measured using the Arizona Life History Battery or a part of it—the Mini-K—as the K-factor. In this study, I examined two research questions regarding the Japanese version of the Mini-K (i.e., Mini-K-J). First, I assessed the construct validity and invariance between sexes of the Mini-K-J because there existed issues with the factor struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…Aggression (Figueredo & Jacobs, 2010), unsafe sexual practices (Figueredo et al, 2006), drug abuse (Brumbach et al, 2009) or deception (Reynolds & McCrea, 2015) are examples of risk-taking behaviors which provide adaptive advantages. In addition, males tend to show fast LHS compared to females (Figueredo et al, 2011(Figueredo et al, , 2013Gladden et al, 2008Gladden et al, , 2013Jonason et al, 2013;Kiire, 2020). Due to their greater variation in reproductive success, males tend to be immersed in reproductive competition, mainly in the form of inter-male competition (Archer, 2009;Betzig, 2012;Ellis et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…Aggression (Figueredo & Jacobs, 2010), unsafe sexual practices (Figueredo et al, 2006), drug abuse (Brumbach et al, 2009) or deception (Reynolds & McCrea, 2015) are examples of risk-taking behaviors which provide adaptive advantages. In addition, males tend to show fast LHS compared to females (Figueredo et al, 2011(Figueredo et al, , 2013Gladden et al, 2008Gladden et al, , 2013Jonason et al, 2013;Kiire, 2020). Due to their greater variation in reproductive success, males tend to be immersed in reproductive competition, mainly in the form of inter-male competition (Archer, 2009;Betzig, 2012;Ellis et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…The original scale measures the relative position of an individual on a continuum of fast and slow strategies based on 20 psychological and behavioral indicators. Mini-K scale is a part of Arizona life history battery which designed to measure individual’s life history strategy [ 102 ]. The reliability and validity of this scale are good [ 103 , 104 ].…”
Section: Methodsmentioning
confidence: 99%
“…A recent meta-analytic study has shown convergent correlations between the Mini-K score and other related measures, including personality, cognitive ability, psychosomatic health, and social relationships, which supports its adequate construct validity [6]. In addition, the Mini-K has been utilized in different international samples, which shows that the Mini-K is a cross-culturally well-validated measurement [15][16][17][18][19][20][21].…”
Section: The Mini-k and Its Characteristicsmentioning
confidence: 96%